Avaliação da microinfiltração marginal em restaurações de resina composta, quando o colágeno dentinário é mantido ou eliminado após o condicionamento ácido, alterando-se o período de armazenamento e a termociclagem - Torres, Carlos Rocha Gomes [UNESP] (2002)
The aim of this study was to evaluate the marginal microleakage in composite resin restorations. under the variables removal or not of the dentin collagen after the acid conditioning, and utilization or not of a flowable composite resin layer on deproteinized dentin, changing the factors: a) storage time (0, 6 and 12 months); b) thermal cycling (500, 1.500 and 2.500 cycles). For this, 180 bovine teeth received class V cavit preparation at cementun-enamel junction. They were assigned to three groups: group C - was applied the Single Bond adhesive system (3M), according to manufacturer instructions, and restored with Z250 composite resin (3M); group H - after the acid conditioning was applied a 10% NaOCI aqueous solution for 1min, and then applied the adhesive and restored with Z250; group HF - like the group H, except that after the adhesive polymerization. a thin layer of a flowable composite resin Natural Flow (DFL) was applied and polimerized, before the placement of Z250. AIl specimens received 500 thermal cycles (5±5'C to 55±5-'C). The specimens in each group were randomly assigned to three subgroups. In the first, the microleakage was evaluated after 24h. In second, the specimens were stored in distillate water containing 0,4% of sodium azide in stove at 37'C, for 6 months, and after this time received more 1.000 thermal cycles. In the third, the specimens were stored for 12 months, and they received more 1.000 thermal cycles for each 6 months. At the end of each storage time, the microleakage was evaluated by the silver nitrate method, followed by cleaning technique. The specimens were analyzed in stereomicroscope and received scores of 0 to 4. The data were submitted to statistical analysis, using the Kruskal Wallis's and Multiple Comparisons tests. After 6 months of storage, the groups H and HF showed falls in microleakage, while the group C didn't showed significant differences